Determinants of Badminton Technical Skills: Integrating Physical Conditioning and Motor Skills Through Structural Equation Modeling - Yuliawan, Dhedhy; Lusianti, Septyaning; Himawanto, Wasis; Bekti, Ruruh Andayani; Nurkholis, Moh. (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Understanding the factors that influence technical skill development in badminton remains an important issue in sport science, as performance in racket sports is shaped by the interaction of physical and motor abilities. Addressing the complex determinants of badminton technical skills is the main objective of this study, which seeks to integrate physical conditioning and motor skills as foundational elements for performance. This study aimed to examine the structural relationship between physical conditioning, motor skills, and badminton basic skills using a Structural Equation Modeling (SEM) approach. Materials and methods. The research employed a quantitative explanatory design involving 76 participants consisting of 57 males and 19 females. Physical conditioning was assessed through standardized physical fitness tests including leg strength, arm strength, endurance, speed, agility, power, flexibility, and balance. Motor skills were measured using the Test of Gross Motor Development-2 (TGMD-2) covering locomotor and object control skills, while badminton basic skills were evaluated through performance tests consisting of service, lob, smash, and wall volley. Data were analyzed using SEM with JASP to examine the relationships among latent variables. Results. The results indicated that the proposed structural model demonstrated good model fit and revealed that physical conditioning and motor skills contribute to the development of badminton basic skills. These findings highlight the importance of integrating physical fitness and motor coordination in developing badminton technical skills. Conclusions. The study implies that training and instructional programs should adopt an integrative approach that combines physical conditioning, motor skill development, and technical practice to optimize skill acquisition in badminton.